Functionalized polyhedral oligomeric silsesquioxane strengthened and toughened bismaleimide resin and composite material, preparation method and application of functionalized polyhedral oligomeric silsesquioxane strengthened and toughened bismaleimide resin
Modified resin was prepared by introducing functionalized cage polysilsesquioxane and diallylbisphenol A into the bismaleimide resin, combined with bismaleimide diphenylmethane, and modified resins were prepared and combined with carbon fibers. Compounding solves the problems of resin brittleness and heat resistance balance, achieves the improvement of strength, toughness and thermal mechanical properties, and is suitable for high-end industrial fields.
Patent Information
- Application Number
- CN202411637631.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-15
AI Technical Summary
Bismaleimide resin is prone to crack propagation and fracture when stress is concentrated, resulting in greater brittleness, limiting its use in applications where high toughness is required, and toughening modification can easily sacrifice heat resistance.
Functionalized cage polysilsesquioxane as toughening agent, combined with diallyl bisphenol A and bismaleimide diphenylmethane, and prepared modified resin by dehydration and condensation method, and compounded with carbon fiber to improve Toughness and thermomechanical properties of the material.
It significantly improves the strength and toughness of the resin, improves the interlayer shear performance of carbon fiber composite materials, maintains or improves the thermomechanical properties, and broadens its application range in aerospace, electronics and electrical appliances, automobile industry and other fields.
Smart Images

Figure CN119264661A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite materials, and in particular relates to a functionalized cage-type polysilsesquioxane-reinforced bismaleimide resin and a composite material thereof, a preparation method and use thereof. Background Art
[0002] Bismaleimide (BMI) is a high-performance thermosetting resin, which is widely used in aerospace, electronics, automotive and other fields due to its excellent heat resistance, chemical resistance, electrical insulation and mechanical properties. BMI contains abundant maleimide double bonds in its molecular structure, which can undergo cross-linking reaction during the curing process to form a highly cross-linked three-dimensional network structure, thus giving the material excellent performance.
[0003] Although BMI resin has many excellent properties, it is brittle and has poor toughness. It is prone to crack propagation and fracture under stress concentration or low temperature environment, which limits its use in certain applications that require high toughness. The brittleness of BMI resin mainly comes from its highly cross-linked rigid network structure. When subjected to external force, stress is concentrated at the crack tip, which easily leads to rapid crack propagation, resulting in brittle fracture of the material. Diallyl bisphenol A has good compatibility in bismaleimide diphenylmethane, which can significantly improve processing performance and toughness. Therefore, BMI resin usually refers to a composite system of the two and has been widely used.
[0004] In order to further improve the toughness of BMI resin, other components can be introduced into the above system to modify BMI, mainly including the following: rubber toughening, introducing rubber elastomer into BMI resin, absorbing energy through deformation of rubber phase, thereby improving the toughness of the material; thermoplastic resin toughening, introducing thermoplastic resin into BMI resin to form a semi-interpenetrating network structure, thereby improving the toughness and impact resistance of the material; inorganic filler toughening, introducing inorganic fillers such as carbon nanotubes and graphene into BMI resin, thereby improving the toughness of the material through interface effect and bridging effect; copolymerization modification, introducing flexible chain segments through copolymerization with other monomers, reducing the crosslinking density of the resin, and improving the toughness of the material.
[0005] However, suitable toughening modification also requires a comprehensive consideration of the balance between the toughening effect and other properties such as heat resistance and processing performance. The biggest advantage of BMI resin compared to the more general epoxy resin is its heat resistance. It is not worth it to sacrifice heat resistance for the sake of toughening. For example, Wang et al. modified BMI resin by bis allyl benzoxazine (Wang Y, Kou K, Zhuo L, et al. Thermal, mechanical and dielectric properties of BMI modified by the Bis allyl benzoxazine [J]. Journal of Polymer Research, 2015, 22: 1-8.). The results showed that although the impact strength of the modified resin was increased to 11.8 kJ / m 2 The flexural strength is increased to 124.1MPa, but its glass transition temperature is reduced to 225℃, which limits its application in high temperature environments.
[0006] By toughening and modifying the BMI resin, the toughness of its carbon fiber composites can also be effectively enhanced, broadening the service life and application range of the composites. But similarly, the strength of the resin itself and the interfacial properties of the composite should not be lost due to toughening the resin. For example, Guo Jizhang introduced thermoplastic resin into the BMI resin for toughening and modification (Research on the Performance of High Modulus and High Strength Carbon Fiber Reinforced BMI Resin-based Composites [D]. Nanchang Hangkong University, 2021.), and its impact strength was increased by about 46%, achieving a good toughening effect, while the heat resistance remained basically unchanged. However, due to the presence of the interlayer toughening structure, the interfacial properties of the toughened modified composite material are relatively poor, resulting in its 90° tensile, 90° compression and interlayer shear properties being lower than those of the untoughened composite material.
[0007] Therefore, providing a toughening method that maintains or even enhances the thermomechanical properties of BMI resin and the interlaminar shear properties of carbon fiber composite materials can not only improve the impact resistance and fatigue resistance of the material, but also enhance the reliability and service life of the material, thereby broadening its application areas. Summary of the invention
[0008] The purpose of the present invention is to provide a functionalized cage-type polysilsesquioxane-reinforced bismaleimide resin and a composite material thereof, a preparation method and use thereof.
[0009] The invention provides a modified resin, which takes functionalized cage-type polysilsesquioxane as a toughening agent and bismaleimide resin as a matrix, wherein the mass of the functionalized cage-type polysilsesquioxane accounts for 0.01% to 10% of the mass of the modified resin.
[0010] Furthermore, the functionalized cage-type polysilsesquioxane is dispersed in a bismaleimide resin matrix as a toughening agent.
[0011] Furthermore, the mass of the functionalized cage-type polysilsesquioxane accounts for 0.05% to 0.3% of the mass of the modified resin, preferably 0.1% to 0.3%.
[0012] Furthermore, its raw materials include functionalized cage-type polysilsesquioxane, diallyl bisphenol A and bismaleimide diphenylmethane; the mass ratio of diallyl bisphenol A to bismaleimide diphenylmethane is 2-4:3-5, preferably 3:4;
[0013] The bismaleimide monomer is selected from bismaleimide diphenylmethane, 1,2-phenylene-bis-maleimide, N,N'-m-phenylene bismaleimide, N,N'-(1,4-phenylene) bismaleimide, N,N'-(4-methyl-1,3-phenylene) bismaleimide, 2,2"-bis[4-(4-maleimidophenoxy)phenyl]propane, and bis(3-ethyl-5-methyl-4-maleimidophenyl)methane.
[0014] Furthermore, the functionalized cage-type polysilsesquioxane is prepared by a dehydration condensation method using a silane compound, and the silane compound is selected from allyltrichlorosilane, octenyltrichlorosilane, chloropropyltrichlorosilane, aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and allyltriethoxysilane.
[0015] Further, the functionalized cage-type polysilsesquioxane is
[0016] The invention also provides a composite material, the raw materials of which include the modified resin and fibers.
[0017] Furthermore, the fiber is selected from carbon fiber, glass fiber, aramid fiber, basalt fiber, polyimide fiber, polyphenylene sulfide fiber, polybenzimidazole fiber, poly(p-phenylene benzobisoxazole) fiber, preferably carbon fiber.
[0018] The present invention also provides a method for preparing the modified resin and composite material, which comprises the following steps: mixing and reacting functionalized cage-type polysilsesquioxane, diallyl bisphenol A and bismaleimide diphenylmethane, and curing to obtain the modified resin; or, mixing and reacting functionalized cage-type polysilsesquioxane, diallyl bisphenol A and bismaleimide diphenylmethane to obtain a resin prepolymer liquid, compounding the resin prepolymer liquid with carbon fiber to prepare a prepreg, and curing to obtain a composite material.
[0019] Further, the reaction temperature is 100-150°C and the reaction time is 0.01-1 hour;
[0020] The curing conditions are: reacting at 140-160° C. for 1-3 hours, reacting at 170-190° C. for 1-3 hours, reacting at 210-230° C. for 3-5 hours, and reacting at 240-260° C. for 3-5 hours.
[0021] Further, the reaction temperature is 140°C and the reaction time is 0.5 hours;
[0022] The curing conditions are: reacting at 150° C. for 2 hours, reacting at 180° C. for 2 hours, reacting at 220° C. for 4 hours, and reacting at 250° C. for 4 hours.
[0023] The present invention also provides the use of the modified resin and composite material in preparing materials in the fields of aerospace, electronic appliances and automobile industries.
[0024] Experimental results show that the present invention uses functionalized cage-type polysilsesquioxane to modify bismaleimide resin to prepare a resin with significantly improved strength and toughness and excellent thermomechanical properties. The interlaminar shear properties of carbon fiber composite materials based on the resin are significantly improved, and the resin has good application prospects in the fields of aerospace, electronics, and automobile industries.
[0025] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0026] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 These are the hydrogen NMR spectrum and solid-state silicon NMR spectrum of octaallyl POSS.
[0028] Figure 2 This is the hydrogen NMR spectrum and solid-state silicon NMR spectrum of octaaminopropyl POSS.
[0029] Figure 3 This is the ILSS cross section of the functionalized POSS modified BDM / DBA and M40J composite material (the left is untreated carbon fiber, the middle is POSS-ally, and the right is POSS-AP). DETAILED DESCRIPTION
[0030] The functionalized cage-type polysilsesquioxane used in the embodiments of the present invention is a commercially available product, or can be prepared by a person skilled in the art through chemical synthesis using known knowledge and experimental means through the following reaction route:
[0031] (1) Preparation of POSS-ally
[0032] 8.78 g of allyltrichlorosilane (ATCS) was dissolved in 50 mL of xylene and stirred with 100 mL of water for 5 hours. After removing the water layer with a separatory funnel, the xylene layer was washed three times with water and 2.4 mL of a phase transfer catalyst (20% benzyltrimethylammonium hydroxide / methanol solution) was added. The mixture was refluxed at 60°C for 4 hours and then left for 4 days. The mixture was refluxed again at 60°C for 24 hours, then cooled and filtered, washed and dried to obtain a white solid powder of octaallyl POSS, denoted as POSS-ally.
[0033]
[0034] (2) Preparation of POSS-AP
[0035] Add 180mL of methanol to a 250mL three-necked flask, then add 10mL of 3-aminopropyltriethoxysilane (APTES) and 15mL of dilute hydrochloric acid (HCl, 36-38%), heat to 70°C and reflux for 19h, add the reaction solution to an equal amount of tetrahydrofuran, the solution immediately turns into a white emulsion, and a white precipitate is formed at the bottom after standing. Wash the precipitate with a 1:1 mixed solvent of methanol and tetrahydrofuran to remove the unreacted raw materials APTES and HCl. After washing several times, vacuum filtration is performed to obtain octaaminopropyl POSS, which is recorded as POSS-AP.
[0036]
[0037] Example 1, preparation of functionalized POSS modified BDM / DBA resin
[0038] POSS-ally was dispersed in methanol to form a uniform solution, 39g of diallyl bisphenol A (DBA) was added at 75°C and stirred for 4h, and then 52g of bismaleimide diphenylmethane (BDM) was added to form a blend of the three, and the mass of POSS-ally was controlled to be 0.1wt% of the total mass of POSS-ally, DBA and BDM. The mixture was prepolymerized at 140°C for half an hour, and vacuum-defoamed at 150°C for 1 hour to obtain a resin casting liquid. The resin casting liquid was cured, and the resin curing system was: 150°C 2h + 180°C 2h + 220°C 4h + 250°C 4h. After annealing, a functionalized POSS-modified BDM / DBA resin casting was obtained, which was recorded as 0.1% POSS-ally.
[0039] Example 2, preparation of functionalized POSS modified BDM / DBA resin
[0040] Referring to the method in Example 1, when preparing functionalized POSS-modified BDM / DBA resin, the only difference is that the mass of POSS-ally is controlled to be 0.05wt%, 0.2wt%, 0.3wt% of the total mass of POSS-ally, DBA and BDM, or, POSS-ally is replaced by POSS-AP and the mass of POSS-AP is controlled to be 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt% of the total mass of POSS-AP, DBA and BDM, to prepare BDM / DBA resin castings with different functionalized POSS modifications, which are respectively recorded as 0.05% POSS-ally, 0.2% POSS-ally, 0.3% POSS-ally, 0.05% POSS-AP, 0.1% POSS-AP, 0.2% POSS-AP, 0.3% POSS-AP.
[0041] Example 3: Preparation of functionalized POSS modified BDM / DBA resin-based carbon fiber composite material
[0042] POSS-ally was dispersed in methanol to form a uniform solution, and then 39g of diallyl bisphenol A (DBA) was added at 75°C and stirred for 4h, and 52g of bismaleimide diphenylmethane (BDM) was added at 140°C for prepolymerization for half an hour, and the mass of POSS-ally was controlled to be 0.1wt% of the total mass of POSS-ally, DBA and BDM, and the resin prepolymer was obtained by vacuum degassing at 150°C for 1 hour. The resin prepolymer was applied to M40J carbon fiber to prepare a prepreg, and then placed in a mold for hot pressing and curing. The resin curing system was: 150°C 2h + 180°C 2h + 220°C 4h + 250°C 4h. After annealing, a functionalized POSS-modified BDM / DBA resin-based carbon fiber composite material was obtained, which was recorded as 0.1% POSS-ally-M40J.
[0043] Example 4: Preparation of functionalized POSS modified BDM / DBA resin-based carbon fiber composite material
[0044] Referring to the method of Example 3, when preparing functionalized POSS modified BDM / DBA resin-based carbon fiber composite materials, the only difference is that POSS-ally is replaced by POSS-AP and the mass of POSS-AP is controlled to be 0.1wt% of the total mass of POSS-AP, DBA and BDM, and 0.1% POSS-AP-M40J is prepared.
[0045] The following comparative samples are prepared by comparative examples.
[0046] Comparative Example 1: Preparation of BDM / DBA resin
[0047] Referring to the method of Example 1, when preparing the functionalized POSS-modified BDM / DBA resin casting, no POSS was added to obtain a BDM / DBA resin casting, which was recorded as BDM / DBA.
[0048] Comparative Example 2: Preparation of BDM / DBA resin-based carbon fiber composite material
[0049] Referring to the method of Example 3, when preparing the functionalized POSS modified BDM / DBA resin-based carbon fiber composite material, POSS was not added to obtain BDM / DBA-M40J.
[0050] The beneficial effects of the present invention are demonstrated by experimental examples below.
[0051] Experimental Example 1: Structural Characterization of POSS-ally and POSS-AP
[0052] 1. Experimental methods
[0053] POSS-ally and POSS-AP were dissolved in deuterated dimethyl sulfoxide and tested by 400 MHz H NMR spectrum, and POSS-ally and POSS-AP powders were directly tested by 400 MHz Si NMR spectrum.
[0054] 2. Experimental results
[0055] Figure 1 It is the hydrogen NMR spectrum and solid NMR silicon spectrum of POSS-ally. From the hydrogen spectrum, it can be seen that the chemical shift from low to high is the peak of the methylene of the cage-type siloxane structure to the hydrogen on the double bond of the allyl group, and the area ratio is 2:1:2, which corresponds to the number of hydrogen atoms.
[0056] In the solid-state NMR silicon spectrum, a sharp single peak can be observed at -82.2ppm, which is a typical T8 structure silicon atom peak. This indicates that all silicon atoms are in the same chemical environment, that is, the product is a completely condensed hexahedral siloxane structure.
[0057] Figure 2It is the hydrogen NMR spectrum and solid-state silicon NMR spectrum of POSS-AP. It can be seen from the hydrogen spectrum that the chemical shifts are from low to high from the cage-type siloxane structure to the methylene and amino peaks of the aminopropyl group, and the area ratio is 1:1:1:1, corresponding to the number of hydrogen atoms. Among them, the chemical shift of amino hydrogen is higher. This is because the formation of hydrogen bonds by organic molecules will reduce the density of the electron cloud around the hydrogen nucleus, resulting in a deshielding effect, which significantly increases the chemical shift of hydrogen on the nitrogen atom that can form hydrogen bonds. Due to the electron pulling effect (inductive effect) of the two nitrogen atoms, the hydrogen spectrum of the hydrogen bond proton appears in the low field position.
[0058] In the solid-state NMR silicon spectrum, a sharp single peak can be observed at -78.3ppm, which is a typical T8 structure silicon atom peak. This indicates that all silicon atoms are in the same chemical environment, that is, the product is a completely condensed hexahedral siloxane structure.
[0059] Experimental Example 2: Performance Characterization of Functionalized POSS Modified BDM / DBA Resin
[0060] 1. Experimental methods
[0061] The resin castings prepared in Examples 1 and 2 were tested for mechanical properties according to the standard GB / T 2567-2021 "Test Methods for Properties of Resin Castings", including tests of tensile, unnotched impact, and bending properties. The dynamic thermomechanical properties were obtained by testing the resin castings on a DMA tester.
[0062] 2. Experimental results
[0063] Tables 1 and 2 show the mechanical properties of BDM / DBA resin modified by POSS-ally and POSS-AP. Among them, the impact strength is the highest when the addition amount of functionalized POSS is 0.3wt%, and the impact strength of 0.3wt% POSS-AP is the highest, which is 11.49kJ / m 2 The elongation at break was the highest when the addition amount of functionalized POSS was 0.1wt%, among which 0.1% POSS-AP had the highest elongation at break, which was 2.32%.
[0064] Table 1 Mechanical properties of octaallyl POSS modified BDM / DBA resin
[0065]
[0066] Table 2 Mechanical properties of octaaminopropyl POSS modified BDM / DBA resin
[0067]
[0068] Table 3 shows the dynamic thermomechanical properties of BDM / DBA resin modified by POSS-ally and POSS-AP. For POSS-ally, 0.1wt% POSS-ally has the highest crosslinking density, and the strength and elongation at break of the material are also the highest. Functionalized POSS plays a "placeholder" role in the bismaleimide crosslinking network, hindering further crosslinking of the network. When the content is high, the crosslinking density of the resin tends to decrease, and the mechanical properties decrease accordingly. With the increase of POSS-AP content, the storage modulus (E') tends to increase first and then decrease. At high temperatures, E' gradually weakens, and the glass transition temperature (T g ) and crosslinking density showed a gradually decreasing trend. The E' of 0.1wt% POSS-AP was the highest, and the tensile strength, elongation at break and flexural strength of the material were also the highest.
[0069] Table 3 Dynamic thermomechanical properties of functionalized POSS modified BDM / DBA resin
[0070]
[0071]
[0072] Experimental Example 3: Characterization of functionalized POSS modified BDM / DBA resin-based carbon fiber composites
[0073] 1. Experimental methods
[0074] The resin-based carbon fiber composite materials prepared in Examples 3 and 4 were tested for interlaminar shear strength according to standard ASTM D2344 to evaluate the interface performance of the composite materials. The interlaminar shear strength (ILSS) reflects the interface debonding performance of the macroscopic composite materials.
[0075] 2. Experimental results
[0076] Table 4 shows the ILSS of functionalized POSS modified BDM / DBA and M40J composites. Figure 3 The ILSS section of the functionalized POSS modified BDM / DBA and M40J composite material (left is untreated carbon fiber, middle is POSS-ally, and right is POSS-AP). It can be seen that the interlaminar shear performance of the composite material is enhanced after toughening by functionalized POSS. Moreover, compared with the 0.1% POSS-ally modified BDM / DBA resin-based carbon fiber composite material, the interlaminar shear strength of the 0.1% POSS-AP modified BDM / DBA resin-based carbon fiber composite material is further significantly improved.
[0077] The functionalized POSS modified BDM / DBA resin-based carbon fiber composite material of the present invention can better adapt to deformation and slow down the speed of crack propagation when shearing occurs.
[0078] Table 4 Interlaminar shear strength of functionalized POSS modified BDM / DBA resin
[0079]
[0080] In summary, the present invention provides a functionalized cage-type polysilsesquioxane-reinforced bismaleimide resin and its composite material, preparation method and use. The present invention adopts functionalized cage-type polysilsesquioxane-modified bismaleimide resin to prepare a resin with significantly improved strength and toughness and excellent thermomechanical properties. The interlaminar shear performance of the carbon fiber composite material based on the functionalized cage-type polysilsesquioxane is significantly improved, and the resin has good application prospects in the fields of aerospace, electronic appliances, and automobile industry.
Claims
1. A modified resin, characterized in that: The modified resin is prepared by taking functionalized cage-type polysilsesquioxane as a toughening agent and bismaleimide resin as a matrix, wherein the mass of the functionalized cage-type polysilsesquioxane accounts for 0.01% to 10% of the mass of the modified resin.
2. The modified resin according to claim 1, characterized in that The functionalized cage-type polysilsesquioxane is dispersed in a bismaleimide resin matrix as a toughening agent.
3. The modified resin according to claim 1, characterized in that The mass of the functionalized cage-type polysilsesquioxane accounts for 0.05% to 0.3% of the mass of the modified resin, preferably 0.1% to 0.3%.
4. The modified resin according to any one of claims 1 to 3, characterized in that Its raw materials include functionalized cage-type polysilsesquioxane, diallyl bisphenol A and bismaleimide monomer; the mass ratio of diallyl bisphenol A to bismaleimide monomer is 2-4:3-5, preferably 3:4; The bismaleimide monomer is selected from bismaleimide diphenylmethane, 1,2-phenylene-bis-maleimide, N,N'-m-phenylene bismaleimide, N,N'-(1,4-phenylene) bismaleimide, N,N'-(4-methyl-1,3-phenylene) bismaleimide, 2,2"-bis[4-(4-maleimidophenoxy)phenyl]propane, and bis(3-ethyl-5-methyl-4-maleimidophenyl)methane.
5. The modified resin according to claim 4, characterized in that The functionalized cage-type polysilsesquioxane is prepared by a dehydration condensation method using a silane compound, and the silane compound is selected from allyl trichlorosilane, octenyl trichlorosilane, chloropropyl trichlorosilane, aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, and allyl triethoxysilane.
6. The modified resin according to claim 4, characterized in that The functionalized cage-type polysilsesquioxane is 7. A composite material, characterized in that Its raw materials include the modified resin and fiber described in any one of claims 1 to 6. Furthermore, the fiber is selected from carbon fiber, glass fiber, aramid fiber, basalt fiber, polyimide fiber, polyphenylene sulfide fiber, polybenzimidazole fiber, poly(p-phenylene benzobisoxazole) fiber, preferably carbon fiber.
8. A method for preparing the modified resin according to any one of claims 1 to 6 and the composite material according to claim 7, characterized in that: The method comprises the following steps: mixing and reacting functionalized cage-type polysilsesquioxane, diallyl bisphenol A and bismaleimide diphenylmethane, and curing to obtain a modified resin; or mixing and reacting functionalized cage-type polysilsesquioxane, diallyl bisphenol A and bismaleimide diphenylmethane to obtain a resin prepolymer liquid, compounding the resin prepolymer liquid with carbon fiber to prepare a prepreg, and curing to obtain a composite material.
9. The method according to claim 8, characterized in that The reaction temperature is 100-150°C and the reaction time is 0.01-1 hour; The curing conditions are: reacting at 140-160° C. for 1-3 hours, reacting at 170-190° C. for 1-3 hours, reacting at 210-230° C. for 3-5 hours, and reacting at 240-260° C. for 3-5 hours.
10. Use of the modified resin according to any one of claims 1 to 6 and the composite material according to claim 7 in the preparation of materials in the fields of aerospace, electronic appliances, and automobile industries.
Citation Information
Patent Citations
Octa-aminopropyl cage type sesquialter siloxane and preparation thereof
CN101503419A
Maleimide with cage-type silsesquioxane structure and synthesis method thereof
CN101723968A
Nanocomposite modification method applied to bismaleimide resin based composite
CN102634208A
Modified bismaleimide resin and preparation method thereof
CN102775605A
High-temperature resistance high-toughness bismaleimide resin as well as preparation method and application thereof
CN108276578A
Cited By
A reactive functional group terminated, POSS core hyperbranched polysiloxane and modified resin composite thereof, method of making and use
CN122772221A